A Treaty held with the Ohio Indians, at Carlisle, in October, 1753 - Peters, Richard, 1704-1776; Norris, Isaac, 1701-1766; Franklin, Benjamin, 1706-1790 (Printed and sold by B. Franklin, and D. Hall, at the new-printing-office, near the market., 1753)
Treaty at Carlisle, which was reported to Governor James Hamilton of Pennsylvania by various Commissioners appointed to negotiate with the Ohio Indians.